A new quasi-dimensional flame tracking combustion model for spark ignition engines. (1st June 2018) - Sjerić, Momir; Kozarac, Darko; Schuemie, Henrik; Tatschl, Reinhard
Highlights: A new quasi-dimensional combustion model is developed. A new approach for the flame geometry is applied. The reduction of local turbulence in the flame reduces local mass burning rate. Simulation results matched well the experimental data of spark ignition engine. Main part of combustion variation is generated during the early combustion phase. Abstract: A new quasi-dimensional combustion model based on the flame tracking approach is described and presented in the paper. The new quasi-dimensional flame tracking model is able to simulate the turbulent combustion process in premixed fuel/air/residual gas mixtures. A new method for the description of the geometry of the combustion chamber and flame front was developed enabling the visualisation of flame front movement across the combustion chamber. The control of local turbulence quantities in the flame front near the wall enables that the developed flame tracking model can predict the entire turbulent combustion process after the flame kernel development in spark-ignition engines without case-dependent calibration requirement. The developed quasi-dimensional combustion model was validated with the experimental and results of multidimensional model of a single cylinder spark ignition engine on averaged cycles. The model was integrated with the previously developed ignition, mixture stratification and cyclic variability sub-model that enable the simulation of cyclic combustion variability triggered by the stochastic variations of flow angle at the spark plug, mixture stratification and in-cylinder turbulence level. Due to the novelty of the model which includes the control of local integral length scale and turbulent kinetic energy in the flame segments the predictive capability of quasi-dimensional model is achieved with the application of single set of parameters related to average cycle and cyclic combustion variability. Flame tracking model with the low computational time represents a promising tool to calculate the turbulent combustion process including cyclic combustion variability in modern spark ignition engines.